2000
DOI: 10.1038/sj.bjp.0703194
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H3 receptors mediate inhibition of noradrenaline release from intestinal sympathetic nerves

Abstract: 1 The present study investigates whether presynaptic histamine receptors regulate noradrenaline release from intestinal sympathetic nerves. The experiments were performed on longitudinal musclemyenteric plexus preparations of guinea-pig ileum, preincubated with [ 3 H]-noradrenaline. 2 In the presence of rauwolscine, electrically-induced [ 3 H]-noradrenaline release was inhibited by histamine or R-a-methylhistamine, whereas it was unaected by pyridylethylamine, impromidine, pyrilamine, cimetidine, thioperamide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 43 publications
(71 reference statements)
3
15
0
Order By: Relevance
“…In keeping with this view, the present results, showing that the inhibitory action of histamine on [ 3 H]acetylcholine release was attenuated by pertussis toxin and abolished by N-ethylmaleimide, suggest that the H 3 receptors, located on cholinergic nerve endings of guinea pig ileum, are coupled to G proteins belonging to G i /G o subtypes. This finding is consistent with the results of previous studies where the involvement of G i /G o proteins was demonstrated for the H 3 receptor-mediated modulation of noradrenergic neurotransmission (Nozaki and Sperelakis 1989;Endou et al 1994;Schlicker et al 1994b;Blandizzi et al 2000).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…In keeping with this view, the present results, showing that the inhibitory action of histamine on [ 3 H]acetylcholine release was attenuated by pertussis toxin and abolished by N-ethylmaleimide, suggest that the H 3 receptors, located on cholinergic nerve endings of guinea pig ileum, are coupled to G proteins belonging to G i /G o subtypes. This finding is consistent with the results of previous studies where the involvement of G i /G o proteins was demonstrated for the H 3 receptor-mediated modulation of noradrenergic neurotransmission (Nozaki and Sperelakis 1989;Endou et al 1994;Schlicker et al 1994b;Blandizzi et al 2000).…”
Section: Discussionsupporting
confidence: 95%
“…In addition, experiments performed on cell lines transfected with human or rat H 3 receptor cDNA indicated a negative coupling of these receptors with adenylyl cyclase in both species (Lovenberg et al 2000). However, studies dealing with histamine-mediated modulation of noradrenergic neurotransmission failed to demonstrate an involvement of cyclic AMP in the signaling pathway of prejunctional H 3 receptors at both central and peripheral level (Schlicker et al 1994b;Celuch 1995;Blandizzi et al 2000).…”
Section: Introductionmentioning
confidence: 95%
“…Preliminary evidence from our laboratory had suggested that G i /G o may be involved in the H 3 R-mediated attenuation of adrenergic inotropic responses in the heart (Endou et al, 1994). Other investigators had also suggested a G i /G o involvement in the H 3 Rmediated inhibition of NE release from intestinal sympathetic nerves (Blandizzi et al, 2000). We therefore determined whether the H 3 R-mediated inhibition of NE exocytosis elicited by K ϩ or forskolin is attenuated by PTX, a Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, activation of the H 3 receptor has been shown to inhibit nerve transmission via cholinergic, noradrenergic and NANC neurons in the ileum, jejunum, duodenum and colon of the guinea-pig gastrointestinal tract (Trzeciakowski 1987;Coruzzi et al 1991;Leurs et al 1991;Poli et al 1991;Taylor and Kilpatrick 1992;Vollinga et al 1992;Hemedah and Mitchelson 1997;Blandizzi et al 2000), human bronchus and guinea-pig trachea (Ichinose and Barnes 1989a;Ichinose et al 1989) as well as from sensory nerves in various tissues (Ichinose and Barnes 1989b;Ohkubo et al 1995).…”
Section: Introductionmentioning
confidence: 97%